Tempo, mente e racconto. La fenomenologia della narrazione come integrazione di mindreading e coerenza globale in una ‘totalità intellegibile’ - Velardi, Andrea (Itinerari, 2024)
The aim of the present paper is to investigate the narrative object suitable for the purpose of ‘thinking (with) literature’. Firstly, we analyze the distinction between popular fiction (PF), which is more based on plot and character’s stereotypization, and literary fiction (LF), where the deepening of psychological aspects prevails in correlation with the improvement of readers’ mentalization skills. Secondly, we analyze the dichotomy between mind-reading and global coherence, as crucial variables in structuring narration, in order to propose an integration and to rediscover the temporal reconfiguration theory of Paul Ricœur and a phenomenology of narration as ‘intelligible totality’ emerging from that integration. Thirdly we propose a comparison with phenomenology of autobiographical memory in order to strengthen our perspective.